The role of the environmental management agency (EMA) in promoting sustainable environment management in Harare South - Mufara, Ratidzo Walford (Midlands State University, 2017)
The study focused on the role of EMA in promoting sustainable environment management in Harare South. In most developing countries, the increase in urbanization has exceeded the development of urban infrastructure and this has led to the multiplying of informal settlements, illegal dumping sites and uncontrolled vending in cities like Harare. The environment has currently become a topical issue globally with climate change, environment degradation and biodiversity loss among the major difficulties. Several Conventions have been ratified and Zimbabwe has also took part in those Multilateral Environment Agreements (MEA) such as the Ramsar Convention and Kyoto Protocol. However despite these efforts the country’s environment is increasingly becoming degraded. The research aimed at the environmental challenges in Harare and how EMA has monitored and regulated environment issues as well as the programs carried out and their impact and effectiveness in improving the environment. A qualitative research method was used to gather information on several environmental issues in the study area. Interviews and observations were carried out to gather information